Enantioselective Alkylation of Amino Acid Derivatives with Unactivated Olefins via C–N Bond Cleavage - Cai, Yue-Ming; Shang, Ming (Synlett, 2022)
We reported a nickel-catalyzed enantioconvergent deaminative alkylation of α-amino acid derivatives with unactivated olefins, providing an efficient and convenient access to a range of α-enantioenriched amides. This method represents the first example of enantioselective deaminative functionalization with racemic amine precursors and features in mild conditions and broad substrate scope. New sterically encumbered bis(oxazoline) ligand was developed to improve both reactivity and enantioselectivity, which is key to the success of this reaction.
Keywords: deaminative alkylation; enantioselective; chiral bis(oxazoline) ligands; α-amino acid; sp3 cross-coupling